(3TQM GdCUhds - (3eLghds
(3ChdgG (B:s
(3HSe Gddg (B.. (3GdNGeS aj JOGNd GdCSHGH GdhGQOI Ydi eSHH hGMO Cj eG bjeI hGMOI bGHdI ddJcQGQ ceG dh MUH dYJb GdQbHI CSHGH eJYOII ef GdXgGQ hGdEaWGQ eKdG HGf bGd Ef XGgQJ aGYJb QbHI hEf CaWQJ aGYJb QbHI (B...s
(3BNQgG (B:s
... (3hGdQNUI jWdb Ydi eYfjf adGHO ef GdJejjR hHjGf Cf GdYRjeI aj JOGNd GdGSHGH GJi eYfi Yf GdeYfjf aJGQI jWdb GdYRjeI hGdQNUI HeYfi eGdG jecf ajg GdGMJjGW CjVG (B...s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3CUhd Gdabgs